Peningkatan Pengetahuan Ibu Tentang Pencegahan Stunting Dan Edukasi Gizi Keluarga Di Desa Bangun Rejo Tahun 2025 - Asnita Sinaga; Dyanti SR Butarbutar; Nova Christiana Sianturi; Dessy Ratna Sari; Deby Chyntia Yun; Astaria Br Ginting (Jurnal Masyarakat Indonesia (Jumas), 2025)
Stunting is a chronic nutritional problem that affects physical growth, cognitive development, and the quality of human resources in the future. Limited maternal knowledge regarding stunting prevention and family nutrition management is one of the major risk factors contributing to stunting among children under five. This community service program aimed to improve mothers’ knowledge of stunting prevention and family nutrition education in Bangun Rejo Village, Tanjung Morawa District, Deli Serdang Regency, North Sumatra Province. The program employed a participatory-educative approach using a pre-test and post-test design involving 67 mothers of under-five children. The intervention included interactive counseling sessions, visual and digital educational media, practical simulations of preparing nutritious meals, and the empowerment of selected mothers as nutrition information agents. The results indicated a significant increase in participants’ knowledge levels; prior to the intervention, 52.2% of participants were categorized as having low knowledge, while after the intervention, 67.2% were categorized as having good knowledge. In addition to improved knowledge, positive changes in attitudes and motivation were observed, particularly in implementing balanced nutrition practices and routine child health monitoring. These findings suggest that a participatory approach is effective in enhancing maternal nutrition literacy and can serve as a community-based intervention model to support stunting reduction programs at the village level.